Cost Efficiency in Japanese Local Governments: the Economic Effect of Information Technology in Japanese Local Governments - Tomoyasu Tanaka (European Regional Science Association (ERSA), 2006)
Due to the current fiscal crisis faced by many Japanese local governments, we decided to conduct research to assist local governments in reducing costs, by reviewing previous studies, as well as investigate the factors affecting wasteful expenditure. Therefore, the purpose of this paper is to analyze the efficiency of local governments in Japan, applying an econometric technique. Further, we calculate indices of cost efficiency using the stochastic cost frontier method. For the purpose of this research we have focused specifically on city areas of municipal governments to examine whether or not information technology contributes to cost efficiency. The hypotheses that we tested were whether or not, the use of information technology equipment and outsourcing of information technology operations by local governments would result in greater cost efficiency. The results show that outsourcing information technology operations increases cost efficiency.
Keywords: 330